Fabrication of pH- and temperature-directed supramolecular materials from 1D fibers to exclusively 2D planar structures using an ionic self-assembly approach1. Issue 14 (14th April 2015) - Gong, Yanjun; Hu, Qiongzheng; Cheng, Ni; Wang, Tao; Xu, Wenwen; Bi, Yanhui; Yu, Li
<x xml:space="preserve">Abstract</x> Constructing multiple-response smart materials is a very interesting and challenging task in materials science.